SISTEM REKOMENDASI PEMILIHAN APLIKASI TERBAIK DI PLAY STORE MENGGUNAKAN SAW BERBASIS WEB - Irfan Fanani , Muhammad; Lazulfa , Indana (Inovate, 2024)
As information technology advances, Android is the most popular operating system among the various options for mobile devices. Since Android apps are open source, developers find it easy to build. Android apps are easy for developers to create because of their open source nature. This will complicate the selection of the ideal application. By creating the best application recommendation system, this problem can be solved. The Simple Additive Weighting (SAW) approach is one way to overcome the problem of selecting the right application. The weighting method is another name for the Simple Additive Weighting (SAW) technique. Finding the weighted total performance rating for each alternative across all categories is a basic principle of the SAW approach. For this approach to work, X's choice matrix must be normalized to a scale that can be compared with all other available alternative ratings. The findings of this study resulted in a web-based application as the final product. The purpose of using this strategy is to make the calculation process simple and easy. To compile various criteria, weighting criteria, variables, matrices, and ranking values based on the SAW technique formula. from the results of this approximation and the results of each calculation, it is suggested that the option with the highest value is selected as the best application. Keywords : Android Application, Recommendation System, Simple Method, Additive Weighting (SAW), Web.